DEVELOPING ENGLISH READING MATERIAL FOR NURSING STUDENTS - Chindy Hanggara Rosa Indah (Jurnal Bahasa Lingua Scientia, 2018)
Developing English reading material for nursing is seen really urgent as the biggest chance for the nursing department graduates to get a job is to go abroad to support the material, the theory of the CTL (Contextual Teaching and Learning) by Johnson (2002) who argues that the learners interwove learning the language and the contents is applied. The development of the reading material adopted from dick & carry (1990) which cover 10 steps and modified become 7 steps. The result of developing English reading material for nursing students covers 1) the picture and word power and reading passage, 2) The exercise of detailed comprehension consists of four kinds of questions. The questions are (a) literal comprehension question, (b) Reorganization which requires the students to analyzed or organize information, involving both summary and paraphrase,(c) inferential comprehension questions,  (d) evaluation which requires the students to compare information and ideas in a text with materials presented by the instructor.